ACTUAL PROBLEMS ENCOUNTERED IN TEACHING FOREIGN LANGUAGES - Qobilova, Kamola (Журнал иностранных языков и лингвистики, 2023)
The article under discussion depicts the main problems in teaching foreign languages. Learning a foreign language contributes, to a certain extent, to the development of the thinking of a student. Genuine knowledge of a foreign language helps the learners to express their thoughts in this language. In order to teach a foreign language as a means of communication, you need to create an atmosphere of real communication, establish a connection between teaching foreign languages and life, and actively use foreign languages in living, natural situations.